Empirical Study of Capital Assets Pricing Model in China Market - Chen, Kai (2014)
The capital asset pricing model appeared in 1970s, it is one of the most important basic theory of modern finance. It is mainly discussed in the securities market risks assets correlations between expected returns and describe the equilibrium state of market risk and asset pricing model in Chinese market, a lot of the empirical results show that does not work, it is often difficult to explain the phenomenon. And domestic scholars in the analysis of data is not the same, the analysis period is different, it leads to their conclusions are diverse from each other. The objective of this paper is to examine whether the capital assets pricing model is efficient to explain the relationship between risk and expected return in China market; to examine whether the capital assets pricing model is more efficient to explain the relationship between risk and expected return in China market than before. This thesis is divided into five chapters. The first chapter is about the research background, research question objective and hypotheses, significant of the study. The second chapter is about literature review on the past research on capital assets pricing model. The third chapter will discuss the research methodology of this study. The fourth chapter is about the data analysis and finding. The last will include the conclusion and recommendation. The empirical result suggest that the capital assets pricing model is inefficient to explain the relationship between risk and expect return in China market now, but it is more efficient than before.